Cytopathological characteristics for provoked lesions of squamous epithelia of digestive system in animal models - V. G. Shestakova; L. I. Nigmatullina; I. B. Atadzhanov; S. A. Donskov; Yu. V. Kozlovskaya; I. S. Dolgopolov; M. Yu. Rykov (Исследования и практика в медицине)
Purpose of the study. Investigation of morphological characteristics of changes in the epithelium of foregut in experimental animals put under conditions of provoked carcinogenesis.Materials and methods. The method of chronic experiment on animals is applied: 40 female non-linear white rats, which are divided into 4 equal groups (n = 10). The first (I) and second (II) control groups of animals were exposed to mechanical trauma of the oral mucosa with additional application of 0.9 % NaCl solution and 1 % aqueous dimethyl sulfoxide (DMSO) solution with a frequency of 2 times a week. The third group of animals, i.e. the main group (4-NQO), was subjected to mechanical traumatization of the oral mucosa with additional application of 1 % DMSO aqueous solution containing 0.1 mg/ml of 4 nitroquinoline-N-oxide, with a frequency of 2 times a week. The fourth group of animals was intact. On the 1st, 7th, 10th, 14th day from the beginning of the experiment, and then every 14 days, cytological material was taken from the oral mucosa and stained with Papanicolaou stain. To compare the emerging changes, the histological picture of the organs of the foregut was studied.Results. Animals from the main group (4-NQO) showed a lag in body weight gain over the standard variance in the control (I and II) and intact groups. Atypical cells of indeterminate significance appeared in smears starting from 42 days of the experiment. Starting from the 56th day of the experiment, atypical cells (1–2 in the field of view), described in Bethesda terms as low-grade intraepithelial lesions, were detected in smears obtained from the main group of animals (4-NQO). Parabasal cells of the squamous epithelium with atypical large (more than 3 times compared to the reference) nuclei, anisonucleosis, with variable contours of the nuclear membrane within one cell, coarse chromatin were recognized as diagnostically significant.Conclusion. The severity of morphological changes in foregut epithelium in the direction of the precancerous state is significantly higher in the main group with prolonged exposure to carcinogenic factor, compared with the control and intact groups (р < 0.05). Thus, the effectiveness of modeling the conditions of provocation of carcinogenesis of the epithelium of the upper digestive tube in experimental animals was studied and proved by mechanical traumatization of the oral mucosa with additional application of carcinogen (4-NQO). This model of provocation of carcinogenesis will be used in the next study of neoplastic processes of the female reproductive system.